Inquérito sorológico de anticorpos anti-Toxoplasma gondii em bovinos de corte do estado de Mato Grosso, Centro-Oeste, Brasil - Maia, Maerle Oliveira (2018)
Toxoplasma gondii is a widely distributed protozoan that infects a wide variety of vertebrates, as well as man, and is one of the most prevalent zoonotic parasites in the world. The infection in humans is due to the ingestion of sporulated T. gondii oocysts and the ingestion of parasitic tissue cysts after the consumption of raw or undercooked meat. To evaluate the prevalence of antibodies anti-T. gondii and associated risk factors, sera from 3,825 cows aged> 24 months belonging to 353 beef farms in the state of Mato Grosso, Brazil, were collected from the Amazon, Cerrado and Pantanal ecoregions during the period from September to December. 2014. An epidemiological questionnaire was applied to each rural producer and anti-T antibodies. gondii were detected by the indirect immunofluorescence (IFA) reaction using a 1:64 cut off dilution. The risk factors associated with the likelihood of the animal being seropositive were analysed through logistic regression. The prevalence of antibodies anti-T. gondii (95% CI, 30.15%, 39.94%) and 92.07% (95% CI, 89.25%, 94, 89%) among the herds. The occurrence of slaughter on the farm was statistically associated with seropositivity in the herd, while cow abortion was a protective factor. Animals raised in the ecoregions of the Amazon and Pantanal were more likely to present with antibodies anti-T. gondii. Therefore, more studies are needed to evaluate the impact of beef on the possible transmission of toxoplasmosis to humans in the region, as well as to establish additional control measures for this protozoan. Future studies should focus mainly on cutting herds created in the Amazon and Pantanal ecoregions, where the highest values of seroprevalence were observed.